Driving Forces of Marine Fisheries and Seafood Export of Bangladesh: Augmented Gravity Model Approach - Fatema, Farha; Islam, Mohammad Monirul (Asian Journal of Economic Modelling, 2020)
Due to the gradual expansion of marine fisheries and seafood trade in the world market, marine economic sectors are emerging as an influential catalyst for the economic growth of Bangladesh as it possesses a long marine water area. This study aims at finding out the driving forces of marine fisheries and seafood export of Bangladesh. It applies augmented gravity model for a panel dataset of 40 countries of 1990-2011 and 17 countries of 2005-2011 for marine fisheries and seafood respectively and uses distance, two dummy variables namely regional trade agreement (RTA) and food safety standards (HACCP) along with some key macroeconomic variables. Some sensitivity tests have been conducted to obtain robust results. The mixed findings suggest that both RTA and HACCP have significant negative impact on the export of marine fisheries whereas RTA shows a positive impact on the export of seafood. Distance does not have a significant impact on either of the cases.